2021
DOI: 10.1017/s000711452100307x
|View full text |Cite
|
Sign up to set email alerts
|

Modified Mediterranean diet v. traditional Iranian diet: efficacy of dietary interventions on dietary inflammatory index score, fatigue severity and disability in multiple sclerosis patients

Abstract: Background Current evidence suggests that adherence to the Mediterranean Diet (MeD) can reduce inflammation in chronic diseases; however, studies pertaining to Relapsing-Remitting Multiple Sclerosis (RRMS) are limited. Therefore, the aim of this study was to investigate the potential of the modified MeD (mMeD) in improving Dietary Inflammatory Index (DII) scores, disability, and fatigue severity, compared to Traditional Iranian Diet (TID), in RRMS patients. Methods After initial screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Bohlouli et al showed that adherence to an anti-inflammatory diet such as the Mediterranean diet improved fatigue severity in relapsing-remitting MS ( 57 ). Cross-sectional studies showed that the body composition and anthropometric measurements were directly associated with DII scores ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bohlouli et al showed that adherence to an anti-inflammatory diet such as the Mediterranean diet improved fatigue severity in relapsing-remitting MS ( 57 ). Cross-sectional studies showed that the body composition and anthropometric measurements were directly associated with DII scores ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study from Iran investigated the potential of a modified MDP to improve dietary inflammatory index scores, disability and fatigue severity, in relapsing-remitting multiple sclerosis compared with a traditional Iranian diet, in 180 patients. Adherence to a MDP for 6 months improved dietary inflammatory status and fatigue severity relative to the traditional Iranian diet (19) . As reviewed by Clark and colleagues, the protective effects of the MDP against inflammation may be in part mediated through favourable changes to the gut microbiota composition and activity (20) .…”
Section: A Mdp Inflammation and Other Chronic Conditionsmentioning
confidence: 95%
“…Emerging evidence is focussing on the relationship between consumption of a MDP and many other chronic diseases (21) , including non-alcoholic fatty liver disease (NAFLD) (22) , cancers and colorectal cancer (23) , multiple sclerosis (19) , as well as positive roles in athletic performance (24) and weight management in pregnancy (25) .…”
Section: A Mdp Inflammation and Other Chronic Conditionsmentioning
confidence: 99%
“…The MSIS-29 examines the physical, cognitive, and psychological impacts of multiple sclerosis on participants' lives; Figure 1A displays the statistical analyses between three studies [62,70,71]. The results of cross-cohort comparisons between MFIS scores, a test for physical and cognitive fatigue, are displayed in Figure 1B [66,[72][73][74]. FIS scores, an older version of the MFIS, were compared from four studies and the results are displayed in Figure 1C [64,73,[75][76][77].…”
Section: Role Of Ga In Preventing Cognitive Decline In Multiple Scler...mentioning
confidence: 99%